Australian women's attitudes towards and understandings of the subdermal contraceptive implant: a qualitative study of never-users. Issue 2 (3rd March 2016) - Inoue, Kumiyo; Kelly, Marguerite; Barratt, Alexandra; Bateson, Deborah; Rutherford, Alison; Black, Kirsten I; Stewart, Mary; Richters, Juliet
Abstract : Objective: Few studies have explored Australian women's understandings of contraception. This study examined the attitudes towards, and understandings of, the subdermal contraceptive implant expressed by women living in New South Wales (NSW), Australia. Study design: As part of a larger qualitative study using in-depth, open-ended interviews in 2012–2013 with women aged 16–49 years who had ever used contraception ( n =94), 65 interviews from women who discussed or mentioned the subdermal implant, but had not previously used the device, were examined and analysed using thematic analysis. Results: The emergent themes were: satisfaction with current method; weak personal opinions and ambivalence; uncertainty due to specific concerns; and strong negative reactions – fear and dislike. Although there were a few positive perceptions expressed by women who had never used the subdermal implant, for the majority of women the perception was predominantly negative. Discussion and conclusion: Women tended to form negative impressions from the stories of other women about the subdermal implant. Interventions to enhance evidence-informed awareness of the relative advantages and disadvantages of the implant – for example, improved access to supportive contraceptive counselling – need investigation in the Australian context. Avenues to improve women's perceived control over the device could also be usefully investigated.